2020
DOI: 10.1093/cid/ciaa918
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Potential Drug–Drug Interactions in Patients of the Swiss HIV Cohort Study in the Era of HIV Integrase Inhibitors

Abstract: Abstract Background Prevalence of potential drug-drug interactions (PDDIs) between antiretroviral drugs (ARVs) and comedications was high in 2008 in a Swiss HIV Cohort Study (SHCS) survey. We reassessed the prevalence of PDDIs in the era of HIV integrase inhibitors (INIs), characterized by more favorable interaction profiles. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 26 publications
3
17
2
Order By: Relevance
“…In contrast to two other studies, which observed stable prevalence of nonrecommended drug combinations in two measurement periods 4 or 10 years apart [7,20], we observed a statistically significant, downward trend in nonrecommended drug combinations, falling from 5.6 to 3.2% between 2010 and 2016. Our findings were consistent with the 1-5.5% prevalence of nonrecommended antiretroviral-comedications reported by others [6][7][8]19,20,38]. Similar to observations in Europe and Australia, the most common, nonrecommended antiretroviral-comedication combinations in BC included boosted antiretrovirals with inhaled corticosteroids and antiplatelet/anticoagulant drugs, and atazanavir or rilpivirine with PPIs [6][7][8][9]19,20,38].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to two other studies, which observed stable prevalence of nonrecommended drug combinations in two measurement periods 4 or 10 years apart [7,20], we observed a statistically significant, downward trend in nonrecommended drug combinations, falling from 5.6 to 3.2% between 2010 and 2016. Our findings were consistent with the 1-5.5% prevalence of nonrecommended antiretroviral-comedications reported by others [6][7][8]19,20,38]. Similar to observations in Europe and Australia, the most common, nonrecommended antiretroviral-comedication combinations in BC included boosted antiretrovirals with inhaled corticosteroids and antiplatelet/anticoagulant drugs, and atazanavir or rilpivirine with PPIs [6][7][8][9]19,20,38].…”
Section: Discussioncontrasting
confidence: 99%
“…The high prevalence of boosted protease inhibitor regimen use in BC (47% in 2016) may also have increased observed drug interaction prevalence. The modest, 14% reduction in overall drug interaction prevalence in BC from 2010 to 2016 was similar to the 16% reduction in observed in the Swiss Cohort between 2008 and 2018 [7,37].…”
Section: Discussionsupporting
confidence: 72%
“…Additionally using more drugs may expose patients to drug‐to‐drug interactions (DDIs) with potentially serious health hazards 5 . While DDIs seem less common with modern ARVs, there are some manageable but unavoidable interactions and some patients require boosting agents; the latter have been associated with a higher risk of DDI due to cytochromes and transporters inhibition 6 …”
Section: Introductionmentioning
confidence: 99%
“…5 While DDIs seem less common with modern ARVs, there are some manageable but unavoidable interactions and some patients require boosting agents; the latter have been associated with a higher risk of DDI due to cytochromes and transporters inhibition. 6 While the clustering of comorbidities has already been studied, little is known about how co-medications cluster in PLWH and controls. 7 This issue may be useful for identifying patients at risk of multiple DDIs and for selecting subgroups having a larger benefit from deprescription of concomitant medications.…”
mentioning
confidence: 99%
“…8 Dolutegravir, which was included in the second antiretroviral regimen of the patient, has a favourable DDI profile because it does not significantly induce or inhibit the cytochrome P450 or glucuronidation systems. 9 For that reason, no DDIs were expected after eplerenone re-initiation.…”
mentioning
confidence: 99%